Assessing communicative performance through a multimodal video project in English for tourism and hospitality - Alan Jaelani; Ninuk Lustyantie; Fathiaty Murtadho (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2026)
In contemporary tourism and hospitality education, communicative competence is increasingly multimodal and digitally mediated. However, conventional assessments often fail to capture this complexity. Thus, this study examines the use of a multimodal video project to assess communicative language performance at a private tourism and hospitality school in Indonesia. The participants were 30 fourth-semester undergraduate students who worked collaboratively to produce short tourism promotion videos integrating spoken language, visual imagery, and audio elements. Data were collected through classroom observations, rubric-based performance assessments, analysis of student-produced video artefacts, and semi-structured interviews with 18 purposively selected students. The assessment focused on key components of communicative performance, including fluency, grammatical accuracy, pronunciation, vocabulary use, coherence, and multimodal integration. Findings revealed that the project provided an authentic assessment context, capturing both linguistic and paralinguistic features, while students highlighted motivation and engagement as critical to their participation. Although perceived as a fair assessment method, challenges in time management, technical skills, linguistic demands, and group coordination emerged. The study advocates for a shift in ESP assessment practices towards incorporating multimodal, performance-based tasks that reflect real-world communication and digital literacy skills.